Kinanthraquinone, a new anthraquinone carboxamide isolated from Streptomyces reveromyceticus SN-593-44. (April 2018) - Takagi, Hiroshi; Nogawa, Toshihiko; Futamura, Yushi; Takahashi, Shunji; Osada, Hiroyuki
Abstract A new anthraquinone derivative, kinanthraquinone (1 ) was isolated fromStreptomyces reveromyceticus SN-593-44. Its structure was determined by the combination of spectroscopic methods including NMR and MS. Kinanthraquinone had a characteristic carboxamide group and was a rare class of metabolite as an anthraquinone derivative isolated from microbes. It showed moderate cytotoxocity against HL-60 andsrc ts -NRK cell with IC50 value of 7.9 and 10 μM, respectively.